X-Ray Photoelectron Spectroscopy on Microbial Cell Surfaces: A Forgotten Method for the Characterization of Microorganisms Encapsulated With Surface-Engineered Shells - Wei, Hao; Yang, Xiao-Yu; van der Mei, Henny C.; Busscher, Henk J. (Frontiers in Chemistry, 2021)
Encapsulation of single microbial cells by surface-engineered shells has great potential for protection of yeasts and bacteria against harsh environmental conditions, such as elevated temperatures, UV-light, extreme pH-values and antimicrobials. Encapsulation with functionalized shells can also alter the surface characteristics of cells in a way that can make them more suitable to perform their function in complex environments, including bio-reactors, bio-fuel production, biosensors and human body. Surface-engineered shells bear as an advantage above genetically-engineered microorganisms that the protection and functionalization added are temporary and disappear upon microbial growth, ultimately breaking a shell. Therewith, the danger of creating a “super-bug”, resistant to all known antimicrobial measures doesnot exist for surface-engineered shells. Encapsulating shells around single microorganisms are predominantly characterized by electron-microscopy, energy-dispersive X-ray spectroscopy, Fourier-transform-infrared spectroscopy, particulate micro-electrophoresis, nitrogen adsorption-desorption isotherms and X-ray diffraction. It is amazing that X-ray-Photoelectron-Spectroscopy (XPS) is forgotten as a method to characterize encapsulated microorganisms. XPS was introduced several decades ago to characterize the elemental composition of microbial cell surfaces. Microbial sample preparation requires freeze-drying which leaves microorganisms intact. Freeze-dried microorganisms form a powder that can be pressed in small cups, suitable for insertion in the high vacuum of an XPS machine and obtaining high resolution spectra. Typically, XPS measures carbon, nitrogen, oxygen and phosphorus as the most common elements in microbial cell surfaces. Models exist to transform these compositions into, biochemical cell surface components, including proteins, polysaccharides, chitin, glucan, teichoic-acid, peptidoglycan and hydrocarbon-like components. Moreover, elemental surface compositions of many different microbial strains and species in freeze-dried conditions, related with zeta potentials of microbial cells, measured in a hydrated state. Relationships between elemental surface compositions measured using XPS in vacuum with characteristics measured in a hydrated state have been taken as a validation of microbial cell surface XPS. Despite the merits of microbial cell surface XPS, it has seldom or never been applied to characterize the different types of surface-engineered shells around yeasts and bacteria currently described in literature. In this review, we aim to advocate the use of XPS as a forgotten method for microbial cell surface characterization, for use on surface-engineered shells encapsulating microorganisms.